Preclinical to Clinical Profile of Curcuma longaas Antidiabetic Therapeutics - Kaushik, Shikha; Masand, Neeraj; Iyer, Malliga R.; Patil, Vaishali M. (Current Topics in Medicinal Chemistry, 2023)
Natural product substances have historically served as the most significant source of new leads for pharmaceutical development. Presently, drug discovery and development have adopted rational approaches to explore herbal resources for treating lifestyle-related diseases such as diabetes. For the treatment of diabetes, Curcumin longa has been extensively studied for evaluation of its antidiabetic potential using various in vivo and in vitro models. Literature resources such as PubMed and Google Scholar have been extensively searched to collect documented studies. Various parts of the plant and extracts have proven antidiabetic effects, namely, anti-hyperglycemic, antioxidant, and anti-inflammatory action, through different mechanisms. It is reported that the plant extract or its phytoconstituents regulate glucose and lipid metabolism. The reported study concluded the diversified antidiabetic role of C. longaand its phytoconstituents and, thus, its potential use as an antidiabetic agent.
Keywords: Curcuma longa